Beyond steroids: A systematic review and proposed solutions to managing acute graft-versus-host disease in adolescents and young adults. (March 2022) - Friend, Brian D.; Schiller, Gary J.
Abstract: The outcomes of allogeneic hematopoietic cell transplantation (HCT) in adolescents and young adults (AYAs) with hematologic malignancies have been shown to be poorer when compared to results in children, due to a combination of higher relapse rates and greater treatment-related mortality (TRM). Although differences in relapse risk have been studied extensively, toxicity has been examined and reported less often. In this systematic review, we summarize recently published studies that have examined the differences in rates of TRM and acute graft-versus-host disease (GVHD) in AYAs and children with hematologic malignancies, and attempt to explain why these disparities exist and how they impact outcomes. In addition, we present best practices for management of steroid-refractory GVHD that are likely to improve survival in this patient population. Further, we propose the development of personalized, risk-based approaches for the prevention and treatment of GVHD that incorporate novel platforms and interventions. We believe this individualized approach is likely to reduce toxicity and greatly improve outcomes for this vulnerable population.